PELAKSANAAN PEMBELAJARAN BERNYANYI DI SMP NEGERI 20 PADANG - Rita Ratna Putri; Jagar Lumbantoruan; Syeilendra Syeilendra (SENDRATASIK UNP, 2018)
AbstractThis article aims to describe the implementation of learning singing in class VII.2 SMP Negeri 20 Padang. The type of research used qualitative research with descriptive method. The object of this research is the Implementation of Singing Lesson in class VII.2 SMP Negeri 20 Padang. The instruments of this study are self-research and researcher assisted with supported instruments such as observation records, interview and photo cameras. Technique of data collecting done by literature review, observation, interview and documentation. The type of data used in this research is primary and secondary data. The result of this research showed that the process of implementation of learning in SMP Negeri 20 Padang was good in singing because of the increasing of  student learning outcomes at the second meeting. The implementation plan of learning has been implemented well during the learning process and it took the time to achieve the learning maximally for practice of singing and also the teacher's knowledge on music theory. The learning of art and culture uses teacher-centered or an expository or spoken learning strategy that is accompanied by direct practice in the classroom. The ability to sing of the students on the song Bungo Parawitan in class VII.2 can be said good because the results obtained from the 30 students or 80% have achieved above average score.Keyword: learning, singing, vocal technique, learning outcomes